2023
DOI: 10.1021/acs.langmuir.2c02843
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Adsorption and Corrosion Inhibition Behavior of Environmentally Friendly Imidazole Derivatives for Copper in the Marine Environment

Abstract: Copper and copper alloys are commonly used in industry due to their excellent mechanical properties, making research on the corrosion resistance of copper of great significance. The corrosion inhibition properties of 2-imidazolidinone and allantoin for copper in 3.5 wt % NaCl were studied by weight loss and electrochemical tests. Changes in the density of the copper corrosion current and the impedance module indicated that 2-imidazolidinone and allantoin exhibited cathodic corrosion inhibitors and a valid prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…VersaStudio software was used to extract the fitting data from the given curves. Likewise, the corrosion inhibition efficiency (η p ) was calculated by the corrosion current density ( i corr ) using the following equation η p = i corr 0 i corr normali corr 0 × 100 % where i corr and i corr 0 are the corrosion current densities with and without the SS inhibitor, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VersaStudio software was used to extract the fitting data from the given curves. Likewise, the corrosion inhibition efficiency (η p ) was calculated by the corrosion current density ( i corr ) using the following equation η p = i corr 0 i corr normali corr 0 × 100 % where i corr and i corr 0 are the corrosion current densities with and without the SS inhibitor, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…VersaStudio software was used to extract the fitting data from the given curves. Likewise, the corrosion inhibition efficiency (η p ) was calculated by the corrosion current density ( i corr ) using the following equation where i corr and i corr 0 are the corrosion current densities with and without the SS inhibitor, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 In particular, imidazole, with a 6π-electron system and high solubility, can intensively interact with metal surfaces, which is used as an effective corrosion inhibitor in pickling, well acidizing, and other operations. 11,12 Zhang et al proposed that the long alkyl chains in imidazoliumbased inhibitors facilitated the formation of dense adsorption films that effectively blocked the contact between metals and corrosive media via hydrophobic shielding. 13 However, many studies have reported the obvious foaming ability of ILs with alkyl chains longer than C 8 , which may adversely affect their practical applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gemini surfactants have two hydrophilic hydrophobic tails and two headgroups connected by rigid or flexible spacers on the head group. , Compared to the conventional gemini surfactants, the imidazolium gemini surfactants have special properties and bigger rigid imidazolium headgroups, which have potential applications in many fields. , For example, they show a stronger self-aggregation performance, better solubility, and thermal stability. They are used to regulate different types of chemical reactions . Therefore, it is of practical interest to study the surface activity of imidazolium gemini surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Compared to the conventional gemini surfactants, the imidazolium gemini surfactants have special properties and bigger rigid imidazolium headgroups, which have potential applications in many fields. 19,20 For example, they show a stronger self-aggregation performance, better solubility, and thermal stability. 21−23 They are used to regulate different types of chemical reactions.…”
Section: ■ Introductionmentioning
confidence: 99%